Parallel Mapping and Catheter Ablation of Polymorphic Premature Ventricular Contractions: A New Feature for Activation Mapping - Moritz Nies; Ruben Schleberger; Leon Dinshaw; Andreas Rillig; Andreas Metzner; Christian Meyer (Case Reports in Cardiology)
We report the case of an 80-year-old female presenting with polymorphic premature ventricular contractions, nonischemic cardiomyopathy, and severe, secondary mitral regurgitation. Despite a low intraprocedural PVC burden, activation mapping and successful ablation of different morphologies were achieved using a novel mapping tool, which facilitates simultaneous mapping of different PVC morphologies.